PERANAN PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN, KESEHATAN, TRANSPORTASI, DAN PERUMAHAN BAGI PEREKONOMIAN INDONESIA - Raynal Yasni; Fuad Iqbal Muhammad (JURNAL RISET TERAPAN AKUNTANSI, 2020)
The purpose of this research is to examine the influence of government expenditure on education, health, transportation and housing and its implication to economics growth in Indonesia. The data is secondary data and processed using error correction model (ECM). The results of this research show that in long term: (1) government expenditure on education, transportation and housing has positive and significant effect on economic growth, (2) government expenditure on health doesn’t have significant effect on economic growth.